Evaluation of DPPH free radical scavenging, α-glucosidase inhibitory, and antimicrobial activities of Aquilaria malaccensis leaf extracts - Abdul Manaf Ali (2021)
Herbs and medicinal plants are major ingredients in traditional or folk medicine for many countries of the world, including Malaysia. This study evaluated the potential of the leaf extract in different solvent polarities and drying methods of Aquilaria malaccensis, in scavenging free radicals and inhibiting the enzyme α-glucosidase as well as antimicrobial activities. Both methanol and ethanol extracts in oven dry method were efficient solvents to extract the antioxidant constituents of A. malaccensis. To analyze α-glucosidase inhibitory activity, the methanol extracts of A. malaccensis in air dry method exhibited the highest activity with an IC₅₀ value of 196.31 μg/mL. In addition, for the antimicrobial activity, each extract was tested by a serial two-fold dilution method against selected Gram-positive bacteria and Gram-negative bacteria, and this suggested that hexane in oven dry method possessed the maximum antimicrobial activity against the gram-positive bacteria tested. It is suggested that the antioxidant and antidiabetic properties were exhibited most in a polar solvent (MEOH) whether in air dry or oven dry method with no significant difference. In contrary with antimicrobial which was efficient in a non-polar solvent (HEX) in oven dry method. These results indicate that A. malaccensis is a promising source as herbal medicine.